La pluralité des logiques de travail dans les tiers-lieux de travail - Frédérique Letourneux (La Nouvelle Revue du Travail, 2022)
The development of new technologies has been accompanied by a proliferation in outsourced forms of work materialising on many organisations’ margins. More and more new work spaces have arisen within this context and are often portrayed as an alternative to workers’ home and corporate lives. Examples include co-working spaces and shared offices. Analysis of co-workers’ practices (and rationale) reveals the different ways in which these “third places” are being used. Such uses depend both on workers’ own professional and biographical characteristics and on the resources that these places provide.